2016
DOI: 10.1002/aenm.201600050
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Stretchable Supercapacitor Using Laser‐Induced Graphene Electrodes onto Elastomeric Substrate

Abstract: (polyimide and polyetherimide) [ 20 ] that cannot provide the suitable mechanical properties required for stretchable energystorage devices.Herein we report a simple method to transfer the LIG porous layer obtained onto polyimide sheet to a transparent and elastomeric substrate such as PDMS (polydimethylsiloxane). Morphology and chemical-physical properties of the obtained material were deeply characterized by electron microscopy investigation, contact angle measurements and vibrational spectroscopy analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
155
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(165 citation statements)
references
References 30 publications
4
155
0
2
Order By: Relevance
“…[33][34][35][36] Meanwhile, we take advantages of the high stretchability and elasticity of silicone rubber, in favor of the practical application of flexibility of MSCs. Compared with the MSCs based on LIG on the polydimethylsiloxane (PDMS) substrate reported in literature, [37] our MSCs present greatly better capacitive and electrochemical properties, and higher stretchability of the devices due to the lower elastic modulus of silicone. Its specific capacity reaches 790 µF cm −2 , which can match with the common MSCs fabricated with graphene synthesized by chemical reaction.…”
Section: Doi: 101002/smll201702249mentioning
confidence: 97%
See 2 more Smart Citations
“…[33][34][35][36] Meanwhile, we take advantages of the high stretchability and elasticity of silicone rubber, in favor of the practical application of flexibility of MSCs. Compared with the MSCs based on LIG on the polydimethylsiloxane (PDMS) substrate reported in literature, [37] our MSCs present greatly better capacitive and electrochemical properties, and higher stretchability of the devices due to the lower elastic modulus of silicone. Its specific capacity reaches 790 µF cm −2 , which can match with the common MSCs fabricated with graphene synthesized by chemical reaction.…”
Section: Doi: 101002/smll201702249mentioning
confidence: 97%
“…Therefore, the devices can be stretched to the length of 400% (Figure 4c and Video S1 (Supporting Information)) and are more flexible than the stretchable supercapacitors onto PDMS (Table S1, Supporting Information). [37] The LIG/silicone rubber layer structure at different strains were observed and the layer becomes thinner ( Figure S5 cannot be ignored that porous space was largely occupied by silicone rubber, leading to smaller electrochemical performance than the LIG on PI. The electrodes at strain states exhibit high resistance, so the capacitance obviously decreases as the tension increases (Table S2, Supporting Information).…”
Section: Doi: 101002/smll201702249mentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, by covering the PI film with a layer of gelatin-mediated ink containing Ni/Co ions, NiO/Co 3 O 4 /LIG patterns could be in situ synthesized during laser writing. [28] The transparency of a logo pattern induced on the PI film and then transferred to the WPU substrate is shown in Figure 1b, which also indicates the convenience and universality of our stretchable MSC fabrication method. [29] The surface morphology evolution of the electrodes during the peeling process are shown in the inset of Figure 1a, suggesting that NiO/Co 3 O 4 /LIG is fully transferred to WPU without much retention.…”
Section: Morphology and Structure Analysismentioning
confidence: 74%
“…[27][28][29][30] For example, Lamberti et al demonstrated PDMS based stretchable MSCs with an areal capacitance of 650 µF cm −2 that showed an 84% capacitance retention after 1000 cycles of stretching. [27][28][29][30] For example, Lamberti et al demonstrated PDMS based stretchable MSCs with an areal capacitance of 650 µF cm −2 that showed an 84% capacitance retention after 1000 cycles of stretching.…”
mentioning
confidence: 99%